Treatment of obstructive jaundice by percutaneous catheterization of the biliary tract - Tiscornia, Eduardo; Sálice, Mario; Delgado, Alicia (Cirugía del Uruguay, 1984)
Percutaneous catheter biliary decompresion offers an efective new radiological alternative to surgical therapy of biliary obstruction.